Dosage Optimization for Letrozole Treatment in Clomiphene-Resistant Patients with Polycystic Ovary Syndrome: A Prospective Interventional Study - Elham Rahmani; Shahnaz Ahmadi; Niloofar Motamed; Hesam_Oddin Maneshi (Obstetrics and Gynecology International)
Objective. Dose adjustment for induction of ovulation is one of the most important problem. Methods. In a prospective interventional study, 44 clomiphene-resistant infertile patients (113 cycles) were selected from the Abolfazl Infertility Clinic of Bushehr University of Medical Sciences. Letrozole was given orally in a dose of 2.5 mg, 5 mg, and 7.5 mg, respectively. If the patient displayed no response, the dosage was increased. Results. In this patients ovulation occurred in 50 cycles (44.24%), clinical pregnancy rate according to number of cycles was 23.89% (27 of 113 cycles) and according to the number of patients was 61.36% (27 of 44 patients). In the 2.5, 5, and 7.5 groups, follicles occurred in 22.9%, 42.1%, and 85.18% of cycles, and pregnancy rate was 14.58%, 28.94% and, 33.33%, respectively. Conclusions. It is better to administer Letrozole at a lower dosage to prevent complications and increase the dose based on sonographic results antral follicular count, anti-Müllerian hormone, LH/FSH, and estradiol.